Ethical Issues in the Response to Ebola Virus Disease in United States Emergency Departments: A Position Paper of the American College of Emergency Physicians, the Emergency Nurses Association, and the Society for Academic Emergency Medicine. (22nd April 2015) - Venkat, Arvind; Asher, Shellie L.; Wolf, Lisa; Geiderman, Joel M.; Marco, Catherine A.; McGreevy, Jolion; Derse, Arthur R.; Otten, Edward J.; Jesus, John E.; Kreitzer, Natalie P.; Escalante, Monica; Levine, Adam C.; et al.
Abstract The 2014 outbreak of Ebola virus disease (EVD) in West Africa has presented a significant public health crisis to the international health community and challenged U.S. emergency departments (EDs) to prepare for patients with a disease of exceeding rarity in developed nations. With the presentation of patients with Ebola to U.S. acute care facilities, ethical questions have been raised in both the press and medical literature as to how U.S. EDs, emergency physicians (EPs), emergency nurses, and other stakeholders in the health care system should approach the current epidemic and its potential for spread in the domestic environment. To address these concerns, the American College of Emergency Physicians, the Emergency Nurses Association, and the Society for Academic Emergency Medicine developed this joint position paper to provide guidance to U.S. EPs, emergency nurses, and other stakeholders in the health care system on how to approach the ethical dilemmas posed by the outbreak of EVD. This paper will address areas of immediate and potential ethical concern to U.S. EDs in how they approach preparation for and management of potential patients with EVD.